A New 2-Step Acceleration Protocol Using a Histone Deacetylase Inhibitor to Generate Insulin-Producing Cells From Adipose-Derived Mesenchymal Stem Cells. Issue 4 (April 2018) - Ikemoto, Tetsuya; Feng, Rui; Shimada, Mitsuo; Saito, Yu; Iwahashi, Shuichi; Morine, Yuji; Imura, Satoru
Abstract : Objectives: We aimed to develop a simple protocol for deriving insulin-producing cells (IPCs) from adipose-derived mesenchymal stem cells (ADSCs). We established a 2-step creation method and an acceleration strategy with a histone deacetylase inhibitor that promoted a pro–endocrine pancreatic lineage. Methods: We seeded ADSCs in 96-well dishes and cultured in Dulbecco's modified Eagle's medium/F12 medium containing 1% fetal bovine serum, 1% B27 supplement, 1% N2 supplement, 50-ng/mL human activin A, and 10-nM exendin-4 for step 1 of differentiation (7 days). Then 10-mM nicotinamide and 50-ng/mL human hepatocyte growth factor, with or without 1 mM histone deacetylase inhibitor, were added for step 2 of differentiation (14 days). After the 2-step differentiation was complete, cell morphology, immunohistochemistry, messenger RNA expression, and function were investigated. Results: Our new differentiation protocol with the histone deacetylase inhibitor significantly accelerated IPC differentiation compared with the conventional protocol without the histone deacetylase inhibitor (median, 21.6 vs 38.8 days; P < 0.05). It also improved the islet morphology score ( P < 0.05) and the glucose stimulation index (3.1). Conclusions: By applying our new and easy 2-step protocol using a histone deacetylase inhibitor, ADSCs may be an effective cell source for differentiation of IPCs.